Oral Dimethyl Fumarate Reduces Peripheral Neuropathic Pain in Rodents via NFE2L2 Antioxidant Signaling. (February 2020) - Li, Jiahe; Ma, Jiacheng; Lacagnina, Michael J.; Lorca, Sabina; Odem, Max A.; Walters, Edgar T.; Kavelaars, Annemieke; Grace, Peter M.
Abstract : Background: Available treatments for neuropathic pain have modest efficacy and significant adverse effects, including abuse potential. Because oxidative stress is a key mechanistic node for neuropathic pain, the authors focused on the master regulator of the antioxidant response—nuclear factor erythroid 2-related factor 2 (NFE2L2; Nrf2)—as an alternative target for neuropathic pain. The authors tested whether dimethyl fumarate (U.S. Food and Drug Administration-approved treatment for multiple sclerosis) would activate NFE2L2 and promote antioxidant activity to reverse neuropathic pain behaviors and oxidative stress-dependent mechanisms. Methods: Male Sprague Dawley rats, and male and female wild type and Nfe2l2 -/- mice were treated with oral dimethyl fumarate/vehicle for 5 days (300 mg/kg; daily) after spared nerve injury/sham surgery (n = 5 to 8 per group). Allodynia was measured in von Frey reflex tests and hyperalgesia in operant conflict-avoidance tests. Ipsilateral L4/5 dorsal root ganglia were assayed for antioxidant and cytokine/chemokine levels, and mitochondrial bioenergetic capacity. Results: Dimethyl fumarate treatment reversed mechanical allodynia (injury-vehicle, 0.45 ± 0.06 g [mean ± SD]; injury-dimethyl fumarate, 8.2 ± 0.16 g; P < 0.001) and hyperalgesia induced by nerve injury (injury-vehicle, 2 of 6 crossed noxious probes; injury-dimethyl fumarate, 6 of 6 crossed; P = 0.013). The antiallodynic effect of dimethyl fumarate was lost in nerve-injured Nfe2l2 -/- mice, but retained in nerve-injured male and female wild type mice (wild type, 0.94 ± 0.25 g; Nfe2l2 -/-, 0.02 ± 0.01 g; P < 0.001). Superoxide dismutase activity was increased by dimethyl fumarate after nerve injury (injury-vehicle, 3.96 ± 1.28 mU/mg; injury-dimethyl fumarate, 7.97 ± 0.47 mU/mg; P < 0.001). Treatment reduced the injury-dependent increases in cytokines and chemokines, including interleukin-1β (injury-vehicle, 13.30 ± 2.95 pg/mg; injury-dimethyl fumarate, 6.33 ± 1.97 pg/mg; P = 0.022). Injury-impaired mitochondrial bioenergetics, including basal respiratory capacity, were restored by dimethyl fumarate treatment ( P = 0.025). Conclusions: Dimethyl fumarate, a nonopioid and orally-bioavailable drug, alleviated nociceptive hypersensitivity induced by peripheral nerve injury via activation of NFE2L2 antioxidant signaling. Dimethyl fumarate also resolved neuroinflammation and mitochondrial dysfunction—oxidative stress-dependent mechanisms that drive nociceptive hypersensitivity after nerve injury. Abstract : Using a rat model of nerve injury, both male and female animals displayed reduced mechanical and nociceptive sensitization when given dimethyl fumarate. Dimethyl fumarate administration increased superoxide dismutase activity while decreasing cytokine expression and improving mitochondrial bioenergetics.Supplemental Digital Content is available in the text.